P08 Routine group and save for elective laparoscopic cholecystectomy. (22nd July 2022) - Jenkin, I; Sulutaura, L; Skan, O; Angheleanu, R; Pizanias, M; Howlader, M; Chohda, E; Lee, H
Abstract: Introduction: Laparoscopic cholecystectomy is the gold standard management for symptomatic cholelithiasis. Intraoperative vascular injury necessitating blood transfusion is a serious but rare complication, typically occurring during dissection around Calot's triangle or trocar insertion. Despite this, standard practice continues to incorporate the obtainment of historic and repeat group and save (G&S) samples to facilitate potential intraoperative transfusion of cross-matched blood. These are relatively expensive (£6.93/sample), time-consuming, and potentially distressing to patients. We review the requirement to obtain routine preoperative G&S samples whilst maintaining patient safety. Methods: We performed a retrospective analysis of all patients having undergone elective laparoscopic cholecystectomy in a single centre during a six-month period in 2021. Seventy-nine patients were identified (53 female; 26 male), with a mean age of 52 years (range 22–80). Results: All patients underwent historic G&S and 73% underwent same-day confirmatory samples. No patients required intraoperative or postoperative blood transfusion. Intraoperative bleeding occurred in two cases but neither required transfusion. Nineteen patients (24%) were admitted postoperatively for reasons including conversion to an open procedure (6%), uncontrolled pain, damage to surrounding structures, and the presence of multiple comorbidities. Conclusion: As such, we propose that routine preoperative G&S samples are not required to undertake safe elective laparoscopic cholecystectomy. In the event of major vascular injury necessitating emergency intraoperative blood transfusion, the major haemorrhage protocol may be activated, and universal donor blood administered. However, routine G&S is recommended in the presence of significant comorbidities (e.g., bleeding diathesis), high likelihood of conversion to an open procedure, or preoperative anaemia. Take-home message: Group and save samples are routinely obtained prior to elective laparoscopic cholecystectomy despite there very rarely being a need for intraoperative or postoperative blood transfusion. Based on our single centre, retrospective cohort study, we propose that such samples need not be obtained aside from in higher risk cases.